The treatment protocol for secondary oligoamenorrhea in women of reproductive age from the perspective of Persian medicine and conventional medicine - Arezoo Moeini Jazani; Mojgan Tansaz; Masoumeh Norouzi Allahleh Korabi; Roshanak Mokaberi Nejad; Morteza Mojahedi; Azam Meyari (Mashhad University of Medical Sciences, 2023)
Introduction: One of the common problems of women in reproductive age is abnormal cessation or reduction of menstrual bleeding, which causes many complications and reduces the quality of life. The present study was conducted with aim to provide a treatment protocol of oligoamenorrhea (secondary amenorrhea, oligomenorrhea) within the framework of the basics of evidence-based Persian medicine and conventional medicine.Methods: In this study, information was collected in the form of narrative review by searching the contents related to cessation or reduction of menstrual bleeding from various Persian medical sources and searching in databases of Pubmed, Web of science, Google scholar, Iranmedex, SID, Magiran with related keywords in order to find evidence and documents. In the next stage, 10 sessions of group discussions on the topic of explanation and interpretation of menstrual disorders in Persian medicine and conventional medicine were held with the presence of experts in the field of Persian medicine and obstetrics and gynecology. Finally, consolidated treatment was presented in the form of a treatment protocol with emphasis on clinical evidences.Results: The principles of oligoamenorrhea treatment in Persian medicine include lifestyle modification, specially nutrition, physical activity, mental and sleep health, use of herbal medicines, and manual operations (which can be integrated with the treatment steps of some causes of this disorder in conventional medicine.Conclusion: Considering the existence of some problems in olioamenorrhea treatment in conventional medicine, the use of Persian traditional medicine in the treatment of oligoamenorrhea along with the protocols of conventional medicine can be helpful in the control and management of this disorder.